Personal information protection in the context of cross-border e-commerce: challenges and systematization - Wang Cong (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
In the context of globalization and digitalization, the rapid development of cross-border e-commerce has promoted the cross-border flow of personal information, but also brought challenges to data security and privacy protection. The cross-border transmission of personal information involves complex legal jurisdiction conflicts, and the regulatory systems of various countries vary significantly. The lack of unified international rules leads to high compliance costs for enterprises. China's "Personal Information Protection Law" and other laws and regulations have established a framework for personal information protection, but there are still problems such as insufficient legal connection and weak industry self-discipline mechanism. In order to optimize the governance system, we can learn from Singapore's "regulatory sandbox" model, promote technological innovation, and strengthen regional cooperation. In the future, it is necessary to balance security and development, establish a hierarchical and classified protection system, and form a governance network of government, enterprise, technology, and international collaboration to protect citizens' rights and promote the sustainable development of cross-border e-commerce.